Environmental preferences and technological choices: Is market competition clean or dirty? - Aghion, Philippe (American Economic Review: Insights)
We investigate the effects of consumers' environmental concerns and market competition on firms' decisions to innovate in "clean" technologies. Agents care about their consumption and environmental footprint; firms pursue greener products to soften price competition. Acting as complements, these forces determine R&D, pollution, and welfare. We test the theory using panel data on patents by 7,060 automobile sector firms in 25 countries, environmental willingness to pay, and competition. As predicted, exposure to prosocial attitudes fosters clean innovation, all the more so where competition is strong. Plausible increases in both together can spur it as much as a large fuel price increase.- Reproduced